2019
DOI: 10.7454/msk.v23i2.9886
|View full text |Cite
|
Sign up to set email alerts
|

Applying bootstrap quantile regression for the construction of a low birth weight model

Abstract: Background: Most investigators use ordinary least squares (OLS) methods to model low birth weight. When the data are non-normal or contain outliers, OLS become ineffective. However, the quantile method of forecasting low birth weight has not been fully evaluated, although it has good potential for overcoming problems associated with linear regression. Methods: The present study reports our comparison between the OLS and quantile regression methods for modeling low birth weight when the data are right skewed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…The empirical data which is used in this study is right skewed or not normal distribution. The appropriate method to model such this data is quantile regression approach [3] [12]. We then combine the Bayesian approach and quantile regression since the size of data is moderate, 150 sample only.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The empirical data which is used in this study is right skewed or not normal distribution. The appropriate method to model such this data is quantile regression approach [3] [12]. We then combine the Bayesian approach and quantile regression since the size of data is moderate, 150 sample only.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile categorical types are residence, education level, and sex of the baby [2]. Descriptives of the data can be seen in Yanuar et al [12]and not presented here because of limited space.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…From a search conducted on several research results, there are factors that influence the occurrence of LBW including pregnant women at the age of less than 20 years or more than 35 years, the distance of pregnancy is too short (less than 2 years), mothers with previous LBW conditions, doing physical work several hours without rest, socioeconomic, poor nutritional status and smokers, drug users and alcohol. Other factors which can also be suspected to influence are parity, the amount of weight gain during pregnancy, prenatal care and haemoglobin concentration [7], [8], [9], [10], [11]. In addition, several studies have shown that there is a fairly close relationship between the incidence of LBW and premature birth [12].…”
Section: Introductionmentioning
confidence: 99%